Development and Test of a Novel Electronic Radiator Thermostat with a Return Temperature Limiting Function - Michele Tunzi; Dorte Skaarup Østergaard; Svend Svendsen (Energies, 2022)
Automated hydronic balancing in space heating systems is crucial for the fourth-generation district heating transition. The current manual balancing requires labor- and time-consuming activities. This article presents the field results of an innovative electronic radiator thermostat tested on two Danish multi-family buildings. The prototypes had an additional return temperature sensor on each radiator and an algorithm was used to accurately control valve opening to ensure automated hydronic balancing. The results highlighted that the new thermostat performed as expected and helped secure the cooling of district heating temperatures —defined as the difference between supply and return temperature—4–12 °C higher during the test compared to results obtained in 2020, when the prototypes were replaced with state-of-the-art thermostats in the first building. The measurements from the other building illustrated how only two uncontrolled radiators out of 175 could contaminate the overall return temperature. The remote connection of the thermostats helped pinpoint the faults in the heating system, although the end-users were not experiencing any discomfort, and secure, after fixing the problems, a return temperature of 35 °C. Future designs may consider integrating a safety functionality to close the valve or limit the flow in case of damage or malfunction to avoid a few radiators compromising the low-temperature operation of an entire building before the cause of the problem has been identified.